Dynamics of Cow's Milk Adulteration Research: Bibliometric Analysis, and Development of SWOT-PESTEL Based Marketing Strategy - Wijaksono, Galih; Dewi, Isti Riana; Asyraf, Abdullah; Hidayah, Asmi Ayuning (Jurnal Ilmu dan Teknologi Hasil Ternak, 2026)
Milk adulteration represents a form of food fraud that compromises product quality and poses significant risks to public health. This study aims to analyze the dynamics of research on cow’s milk adulteration through a bibliometric approach and to formulate development strategies using SWOT-PESTEL analysis. Data were collected from Google Scholar via Publish or Perish, covering publications from 2016 to 2026, resulting in 304 articles analyzed with VOSviewer.  The SWOT-PESTEL analysis was developed through a synthesis of bibliometric findings and a systematic literature review and was subsequently critically interpreted by the authors based on the available scientific evidence. The findings indicate that research on milk adulteration has shown a rising trend, with the focus shifting from traditional adulterant detection toward the application of modern technologies such as FTIR, NIR, Raman spectroscopy, and HPLC-MS/MS. The SWOT analysis highlights modern detection technologies as a key strength, while limited access to technology and inadequate supply chain monitoring remain major weaknesses. The PESTEL analysis underscores the importance of regulatory support, consumer education, technological innovation, and strengthened quality control systems. The integration of advanced detection technologies, product traceability systems, and comprehensive food safety policies is essential to enhance the safety, authenticity, and competitiveness of cow’s milk.